2007
DOI: 10.1017/s1751731107000067
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fish oil supplementation of pregnant and lactating ewes on milk production and lamb performance

Abstract: Supplementation of pregnant ewes with long-chain n-3 polyunsaturated fatty acids (PUFA) demonstrably improves indicators of neonatal lamb vigour, potentially improving the number of lambs reared per ewe. The present study investigated the effect of supplementing ewes with fish oil and vitamin E (a-tocopherol acetate) throughout both pregnancy and lactation on the performance of lactating ewes and sucking lambs. Forty-eight ewes were supplemented with one of four concentrates containing either Megalac or fish o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 43 publications
7
35
1
Order By: Relevance
“…The significant increase in plasma 20:5n3 and 22:6n3 in ewes offered diets containing fishmeal were a direct result of the increased dietary supply of preformed VL_n3-PUFA and in agreement with Capper et al (2007). However, our study was carried out with a limited number of experimental units.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The significant increase in plasma 20:5n3 and 22:6n3 in ewes offered diets containing fishmeal were a direct result of the increased dietary supply of preformed VL_n3-PUFA and in agreement with Capper et al (2007). However, our study was carried out with a limited number of experimental units.…”
Section: Discussionmentioning
confidence: 79%
“…A specific functional role of DHA had been shown in the fetus and early infant neural development, which might influence neonatal viability (Cattaneo et al, 2006;Capper et al, 2007). Docosahexaenoic acid is highly concentrated in brain tissues and selectively accumulated during later stages of fetal development and infant brain growth (Brenna and Lapillonne, 2009;Hsieh and Brenna, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (Appeddu et al, 2004;Capper et al, 2007) have reported either small or no changes in suckling lamb performance when lactating ewe diets were supplemented with calcium soaps or fish oil. Furthermore, researchers indicated that changes in suckling lamb performance are mainly related to differences in milk yield, as well as milk fat and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, inclusion of certain oils, especially fish oils, has been shown to reduce both milk yield and milk fat concentrations in the dam (Capper et al, 2007), which could potentially reduce suckling lamb growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research has focused on the benefits of lipid supplementation on the PUFA content of lamb meat but its effects on animal performance and carcass composition, which are of greatest economic importance, have received little attention. Supplementing ewes with fish oil during pregnancy and lactation has been shown to improve neonatal lamb vigour (Capper et al, 2006) but depresses milk yield and fat concentration (Annett et al, 2008 and, which can reduce growth rate of their lambs (Capper et al, 2007;Annett et al, 2008). There is also evidence that PUFA supplementation can reduce dry matter intake (DMI) in sheep (Annett et al, 2008), which could further impinge on lamb growth and make these feeding strategies uneconomical.…”
Section: Introductionmentioning
confidence: 99%